O brincar para conhecer o desenvolvimento de crianças com implante coclear - Magalhães, Aracê Maria Magenta; Bomtempo, Edda; Peréz-Ramos, Aidyl M. de Queiroz; Salgado, Manoel Henrique [UNESP] (My University, 2012)
This research analyses the development of children presented with profound deafness and benefited by the cochlear implant, discovery of great significance in hearing health. The work is based, theoretically, on Winnicott, and methodologically, in anamnesis data and playing on a set of ludic scenes, systematically organized. Ten pre-school children with implants, selected by hospital and homogenization eligibility criteria participate in this study encompassing interviews with parents and playful observation sessions with the children, besides Lynn´s Dolls Structured Game. In the children, the results show immaturity, regression to earlier stages of their development, dependency and behavioral disorders, in particular, those related to language, interrelationship and anxiety. In the parents, family disorientation, partly overcome. The children and family participating are assisted by a multidisciplinary health team, at the hospital where they are attended.

Esta pesquisa analisa o desenvolvimento de crianças com surdez profunda e beneficiadas pelo implante coclear, uma descoberta de grande significação na saúde audiológica. O trabalho fundamenta-se, teoricamente, em Winnicott e, metodologicamente, em dados de anamnese e do brincar em um conjunto de cenas lúdicas, sistematicamente organizadas. Dez pré-escolares com implante, selecionados por critérios de elegibilidade hospitalar e de homogeneização, são participantes deste estudo. Utilizam-se entrevistas com os pais e realizam-se sessões de observação lúdica e o Jogo Estruturado com Bonecos, de Lynn, nas crianças. Os resultados evidenciam, nessas últimas, imaturidade, regressão a fases anteriores de seu desenvolvimento, dependência e distúrbios de comportamento em especial os de linguagem, inter-relação e ansiedade; nos pais, desorientação familiar, em parte, superada. As crianças e as famílias participantes são assistidas por uma equipe multidisciplinar de saúde, no hospital onde são atendidas.
Keywords: Child; Winnicott; Cochlear implant; Lynn’s structured doll play test; Crianças; Winnicott; Implante coclear; Jogo estruturado com bonecos de Lynn